2012
DOI: 10.1166/jnn.2012.5142
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Antimicrobial Activity of Nano-Hydroxyapatite-Zinc for Bone Tissue Engineering Applications

Abstract: The bone implants used in tissue repair are susceptible to infections caused by staphylococci, specifically Staphylococcus aureus. Hence, the development of better biological materials that provide antimicrobial activity in bone tissue engineering is required. The nanoparticles of hydroxyapatite (nHAp) and nHAp dopped with Zn (nHAp-Zn) were prepared by the wet chemical method and the ion exchange method, respectively. They were characterized using SEM, AFM, FTIR and XRD. The antibacterial activity of nHAp and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 0 publications
0
14
0
2
Order By: Relevance
“…It can also promote bone metabolism, growth, mineralization, increase bone density and prevent bone resorption 6) . Researches confirmed that the calcium phosphate ceramic coatings containing zinc promoted biological activity of osteoblasts than the pure HA coating in vitro 7) . It can also be used as antimicrobial elements, and showed good anti-bacterial activity 8).…”
Section: Introductionmentioning
confidence: 81%
“…It can also promote bone metabolism, growth, mineralization, increase bone density and prevent bone resorption 6) . Researches confirmed that the calcium phosphate ceramic coatings containing zinc promoted biological activity of osteoblasts than the pure HA coating in vitro 7) . It can also be used as antimicrobial elements, and showed good anti-bacterial activity 8).…”
Section: Introductionmentioning
confidence: 81%
“…only as a bone-forming agent [10], but also as a microbial agent [11,12], as a drug delivery system [13], as a coating [14] and as a biomarker for nanomedical applications [15,16].…”
mentioning
confidence: 99%
“…Modifikacija HAp-a dopiranjem ili supstitucijom anjona ili katjona proširuje potencijalnu biomedicinsku primenu ovog materijala. Metal-dopirani HAp pokazao je veliki osteogenetski potencijal [22], takođe i antimikrobna svojstva [23], a može biti pogodan i za dobijanje prevlaka [24], sistema za dostavu medikamenata [25], biomarkera za nanomedicinske aplikacije [26], itd. Katjon poput Ca 2+ i anjoni poput PO4 3-i OH -jona, iz strukture HAp-a, se mogu delimično ili potpuno zameniti drugim jonima, bez narušavanja kristalografske simetrije.…”
Section: Slika 3 -Uticaj Temperature Ph Vrednosti I Vremenaunclassified